2022
DOI: 10.1111/eea.13179
|View full text |Cite
|
Sign up to set email alerts
|

Repellent activity of trans‐anethole and tea tree oil against Aedes aegypti and their interaction with OBP1, a protein involved in olfaction

Abstract: Mosquitoes act as vectors for the transmission of various infectious pathogens. The associated diseases are prevalent in tropical and subtropical regions of the world and can be prevented by effective vector control and management. Natural compounds have become a potential alternative to synthetic repellents that are unsafe and harmful to the environment. The repellent activity of trans‐anethole and tea tree [Melaleuca alternifolia (Maiden & E. Betche) Cheel, Myrtaceae] oils was tested against the vector Aedes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…7,9,11,38 SARs showed that Propenylbenzene, such as anethole, has a broad range of biological activities against insect vectors, which had been represented in different insecticidal chemistry areas. 16,24 Based on a rationally conceived pharmacophore model, substituted propenylbenzene groups were introduced at the 1-position of the mesoionic core and explored the SAR (Tables 4−6). Although many types of substitutions in the propenylbenzene ring were tolerated, unsubstituted propenylbenzene remained the most potent compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9,11,38 SARs showed that Propenylbenzene, such as anethole, has a broad range of biological activities against insect vectors, which had been represented in different insecticidal chemistry areas. 16,24 Based on a rationally conceived pharmacophore model, substituted propenylbenzene groups were introduced at the 1-position of the mesoionic core and explored the SAR (Tables 4−6). Although many types of substitutions in the propenylbenzene ring were tolerated, unsubstituted propenylbenzene remained the most potent compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In order to optimize the mesoionic lead compound, 2,2,2-trifluorethyl and (2-chlorothiazol-5-yl)­methyl group replace the n -propyl group at the 1-position of the mesoionic core based on bioisosteric replacement strategy (compounds 2 and 3 ) showing excellent insecticidal activity against many kinds of pests . Further optimization based on compound 3 led to the discovery of triflumezopyrim ( 4 ) and dicloromezotiaz ( 5 ) as a hemiptera and lepidoptera insecticide by the bioisosteric replacement strategy (Figure ), , which exert their insecticidal action by inhibiting nicotinic acetylcholine receptors (nAChRs). Also, the nAChRs play a central role in fast excitatory synaptic transmission in the insect central nervous system and have been an important neuronal target for the control of vector insects. , As a highly efficient pharmacophore, anethole has a broad range of biological activities against vector insects, including mosquitoes, Rhipicephalus microplus, Rhipicephalus annulatus, and Dermacentor nitens, , Myzus persicae, , Musca domestica, Bemisia tabaci, and Periplaneta americana, with neurotoxic actions of acetylcholinesterase, GABA receptors, and octopamine receptors. It is a potential chemical probe and a lead candidate for the development of insect vector control agents …”
Section: Introductionmentioning
confidence: 99%